Utilização de áreas de preservação permanente como instrumento pedagógico para as ações em educação ambiental - Farias, Ezequiel Sóstenes Bezerra (2018)
Recovery projects in degraded areas should be linked to the Environmental Education didactic practices, in which the assisted public (rural or urban) can be stimulated, through formal and non-formal practices, to develop cognitive capacities that make them able to sustainable interventions and critical reading of geographical spaces. In this sense, by promoting the recovery of a section of riparian forest located on the banks of the Paraíba do Norte River, young people from the city of Camalaú, Paraíba, were included to assess the extent to which the non-formal education process can raise awareness and help to understand the need for preservation and recovery of these areas. This work is made up of a study carried out with thirty students of the State School of Primary and Secondary Education Pedro Bezerra Filho between the months of February 2017 to February 2018 in an experimental unit in Sítio Viegas. The sample consisted of students from the three series of the day and night periods, randomly divided into three classes. The methodological procedures consisted of three evaluations with open and closed questions, addressing the following thematic areas: Living and Living in the Brazilian Semi-arid, Management and Conservation of the Caatinga and Recovery of Ciliary Forest through Agroforestry Systems. The evaluations were carried out separately with three distinct classes, the first being composed of students who attended theoretical and practical classes; the second with students who only attended theoretical classes and the third with students who did not attend any classes offered by the project, the latter being the witnessing group of the analysis. Through the present study it is possible to observe the efficiency of the non-formal spaces in the cognitive gain of the students, allowing numerous practices that can serve as a didactic instrument in the moments of knowledge construction. It was verified that the field classes responded positively as technical / pedagogical support in teaching activities and developed abilities of environmental perception, oral communication, geographical space reading, content domain, group leadership, team planning, technical observation and scientific experimentation. Therefore, the vast majority of potential agro-ecological multipliers of the Brazilian semi-arid region. It is concluded from this study that it is necessary to intensify in a positive way the field experiences in the teaching practices of educational institutions.